2022
DOI: 10.3892/mmr.2022.12771
|View full text |Cite
|
Sign up to set email alerts
|

A novel 7‑hypoxia‑related long non‑coding RNA signature associated with prognosis and proliferation in melanoma

Abstract: Hypoxia-related long non-coding RNAs (lncRNAs) are important indicators of the poor prognosis of cancers. The present study aimed to explore the potential relationship between melanoma and hypoxia-related lncRNAs. The transcriptome and clinical data of patients with melanoma were downloaded from The Cancer Genome Atlas database. The prognostic hypoxia-related lncRNAs were screened out using Pearson's correlation test and univariate Cox analysis. As a result, a hypoxia-related-lncRNA signature based on the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It has reported that MIR205HG is upregulated in melanoma [ 13 , 23 ]. The expression pattern of MIR205HG was determined in cultured cell lines and the results showed the upregulation of MIR205HG expression in melanoma cells ( P < 0.01, Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…It has reported that MIR205HG is upregulated in melanoma [ 13 , 23 ]. The expression pattern of MIR205HG was determined in cultured cell lines and the results showed the upregulation of MIR205HG expression in melanoma cells ( P < 0.01, Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we rst obtained lncRNAs related to amino acid metabolism by co-expression analysis of lncRNAs and amino acid metabolism-related genes, and then used one-way and multi-way Cox regression analysis to obtain a total of LINC02870, AL031985.3, AC011476.3, AC012640.1, AL365361.1 and LUCAT1 and 6 prognosis-related lncRNAs,and prognostic features were constructed.The results of ROC,Kaplan-Meie curve,column line plot and heat map analysis showed that the risk score of the features was an independent predictor for patients with hepatocellular carcinoma and also for patients with different clinical stages,and could reliably predict the prognosis of patients with hepatocellular carcinoma. Among these six amino acid metabolism-related lncRNAs, LINC02870 has been previously reported as hepatocellular carcinoma stem cell and necroptosis-related lncRNA in hepatocellular carcinoma and was signi cantly associated with patient prognosis [32,33] , AC012640.1 can be used to predict the prognosis of patients with alcohol-associated hepatocellular carcinoma [34] , and AL365361.1 is an oncogene that is involved in the prognosis of tumor patients with clear cell renal cell carcinoma, ovarian cancer and melanoma [35][36][37] . AL031985.3 can similarly be involved as a scorch death, iron death and immune-related lncRNA in hepatocellular carcinoma to in uence patient prognosis [38,39] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we rst obtained lncRNAs related to amino acid metabolism by co-expression analysis of lncRNAs and amino acid metabolism-related genes, and then used one-way and multi-way Cox regression analysis to obtain a total of LINC02870, AL031985.3, AC011476.3, AC012640.1, AL365361.1 and LUCAT1 and 6 prognosis-related lncRNAs,and prognostic features were constructed.The results of ROC,Kaplan-Meie curve,column line plot and heat map analysis showed that the risk score of the features was an independent predictor for patients with hepatocellular carcinoma and also for patients with different clinical stages,and could reliably predict the prognosis of patients with hepatocellular carcinoma. Among these six amino acid metabolism-related lncRNAs, LINC02870 has been previously reported as hepatocellular carcinoma stem cell and necroptosis-related lncRNA in hepatocellular carcinoma and was signi cantly associated with patient prognosis [32,33] , AC012640.1 can be used to predict the prognosis of patients with alcohol-associated hepatocellular carcinoma [34] , and AL365361.1 is an oncogene that is involved in the prognosis of tumor patients with clear cell renal cell carcinoma, ovarian cancer and melanoma [35][36][37] . AL031985.3 can similarly be involved as a scorch death, iron death and immune-related lncRNA in hepatocellular carcinoma to in uence patient prognosis [38,39] .…”
Section: Discussionmentioning
confidence: 99%